The Total Cholesterol And Body Weight Lowering Effect Of Wild Poinsettia Infusion (Euphorbia heterophylla L.) On The High Fat – Diet Induced Rats - Novembrina, Metrikana; Wahyuni, Tri; Anggrahini, Siti Nur Muthia; Toyo, Eleonora Maryeta; Serang, Yithro (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Obesity is one of the risk factors which can lead to cardiovascular diseases such as hypertension, diabetes melitus and end stage renal failure. As a tropical archipelago, Indonesia has abundant potential of medicinal plantsuch as Wild Poinsettia (Euphorbia heterophilla L.), which is used by the locals as anherbal drinking to treat obesity. This research aimed to study the effectivenes of Wild poinsettia infusion in lowering total cholesterol level and body weight on the high fat – diet induced wistar male rats. The study used an experimental method with controlled post-test only design. As many as 30 high fat-diet induced male wistar rats were devided into six groups : normal control, negative control given 0,5% cmc Na as placebo, positive control given 27 mg/kgBB gemfibrozil and those given 1.25g/kgBW, 2.5g/kgBW and 5 g/kgBW Wild poinsettia infusion respectively. Prior to the treatment, the total cholesterol level of all groups were measured by using NESCO GCU®cholesterol test kit. After the treatment, the cholesterol levels were remeasured. The body weight of all testing animal was measured every week. Data was then collected and analyzed by using anava to evaluate the difference of total cholesterol level and body weight among the testing groups. According to data analysis’s results, it showed that the bodyweight and the total cholesterol level of all testing groups were significantly different (p < 0,05). Based on the results it was concluded that the Wild poinsettia infusion given to the high fat-diet induced rats can lower their total cholesterol level as well as the body weight. Keywords: high fat-diet induced rats, wild poinsettia infusion, obesity.